ECHINOCOCCUS AND ITS IMPORTANCE IN SURGERY (LITERATURE REVIEW) (World Bulletin of Public Health, 2024)
The article presents a review of the literature on one of the urgent problems of surgery. Echinococcal disease is widespread in many countries of the world. According to some estimates, more than 1 million people are currently affected by echinococcosis in the world, while the incidence in some endemic and nonendemic regions differs by more than 200 times [1]. In the last decade, there has been an increase in the incidence of echinococcosis and the expansion of the geographical boundaries of the disease. Despite the improvement of surgical intervention techniques using modern technologies, the introduction of various chemical and physical methods of influencing the parasite, the frequency of recurrence of echinococcosis remains high. However, this is the basis for a deeper study of the problem.